2012
DOI: 10.1074/jbc.m112.352336
|View full text |Cite|
|
Sign up to set email alerts
|

Caveolin-1 Inhibits Expression of Antioxidant Enzymes through Direct Interaction with Nuclear Erythroid 2 p45-related Factor-2 (Nrf2)

Abstract: Background: Caveolin-1 regulates cellular antioxidant capacity, but mechanisms remain unknown. Results: Caveolin-1 interacts with Nrf2 and suppresses its transcriptional activity and down-regulates cellular antioxidant enzymes. Conclusion: Caveolin-1 regulates cellular antioxidant capacity through interaction with Nrf2. Significance: Clarifying how caveolin-1 regulates cellular antioxidant capacity and identifying a novel target to establish the contribution of oxidative stress to human pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 37 publications
2
54
0
4
Order By: Relevance
“…The typical Cav-1-protein interaction occurs through the scaffolding domain in Cav-1 and the CBM in target proteins, such as endothelial nitric oxide synthase (11), Tolllike receptor 4 (40), and activin receptor-like kinase 1 (37). We have recently observed that the autophagy protein LC3B and transcription factor nuclear erythroid 2 p45-related factor-2 (Nrf2), respectively, contain amino acid sequences very similar to CBM, and these similar structures mediate the interactions of Cav-1-LC3B (4) and Cav-1-Nrf2 (22). In the present study, we have also found that a typical CBM is presented in ATG12, which also mediates its interaction with Cav-1, as mutation of the CBM in ATG12 effectively disrupted their association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical Cav-1-protein interaction occurs through the scaffolding domain in Cav-1 and the CBM in target proteins, such as endothelial nitric oxide synthase (11), Tolllike receptor 4 (40), and activin receptor-like kinase 1 (37). We have recently observed that the autophagy protein LC3B and transcription factor nuclear erythroid 2 p45-related factor-2 (Nrf2), respectively, contain amino acid sequences very similar to CBM, and these similar structures mediate the interactions of Cav-1-LC3B (4) and Cav-1-Nrf2 (22). In the present study, we have also found that a typical CBM is presented in ATG12, which also mediates its interaction with Cav-1, as mutation of the CBM in ATG12 effectively disrupted their association.…”
Section: Discussionmentioning
confidence: 99%
“…3B). In fact, we have recently observed that, in Beas-2B cells, Cav-1 distributed majorly in cytosol as well as in nucleus (22).…”
Section: Atg12-atg5 Interacts With Cav-1 In Cytosolmentioning
confidence: 93%
“…In ovarian carcinoma cell lines, Cav-1 regulates cell cycle regulatory gene expression through direct DNA binding (37). Cav-1 also affects transcription in lung epithelial Beas-2B cells by directly binding the transcription factor nuclear erythroid 2 p45-related factor 2 (Nrf2) (38). Our previous work (17) revealed an interaction between Cav-1 and GR in NPSCs.…”
Section: Resultsmentioning
confidence: 96%
“…We employed an RNAi-based approach utilising previously published siRNA which we have previously employed to silence expression of aadaptin, a critical component of the clathrin-mediated endocytosis machinery, in HeLa cells (Rappoport and Simon, 2008;Rappoport and Simon, 2009), or caveolin1 (Li et al, 2012), which is required for caveolae formation (Rothberg et al, 1992). Control experiments revealed that a-adaptin siRNA treatment significantly inhibited transferrin endocytosis (supplementary material Fig.…”
Section: Fgfr Is Internalized Through Clathrin-mediated Endocytosismentioning
confidence: 99%